2020
DOI: 10.1186/s12885-020-07225-1
|View full text |Cite
|
Sign up to set email alerts
|

UGT1A1 polymorphism has a prognostic effect in patients with stage IB or II uterine cervical cancer and one or no metastatic pelvic nodes receiving irinotecan chemotherapy: a retrospective study

Abstract: Background Uridine diphosphate glucuronosyltransferase 1 family polypeptide A1 ( UGT1A1 ) is a predictive biomarker for the side-effects of irinotecan chemotherapy, which reduces the volume of tumors harboring UGT1A1 polymorphisms. We aimed to determine whether UGT1A1 polymorphisms can predict progression-free survival in patients with local cervical cancer treated with irinotecan chemotherapy. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Cervical cancer is a malignant tumor that occurs in the cervix, vagina, and cervical canal. It is the most common reproductive tract cancer [12]. The incidence rate of malignant tumors is the second of gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is a malignant tumor that occurs in the cervix, vagina, and cervical canal. It is the most common reproductive tract cancer [12]. The incidence rate of malignant tumors is the second of gynecologic malignancies.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 38 A recent study also found that neither UGT1A1*6 nor *28 had an impact on treatment efficacy and PFS in metastatic CRC; 34 however, Matsuoka et al suggested that UGT1A1 polymorphisms were significantly related with longer PFS in uterine cervical cancer. 39 Similarly, the findings by Henriksen et al revealed that UGT1A1*28 improved the PFS and OS in metastatic renal cell carcinoma. 40 In contrast, the study by Yamaguchi et al confirmed that UGT1A1*6 and *28 were shown to be related to a shorter OS in advanced gastric cancer when irinotecan monotherapy was used as a third-line treatment.…”
Section: Discussionmentioning
confidence: 87%
“…Applying the exclusion criteria, 195 articles were removed and the remaining 105 full‐text articles were assessed in depth in line with the predetermined eligibility criteria. Finally, 42 articles were included in the meta‐analysis for assessing the associations of UGT1A1*6/UGT1A1*28 or ABCC2 c.3972C>T with irinotecan‐induced severe toxicities 12,14,21–24,26–31,34,35,48–75 . The complete selection process for the articles following PRISMA guidelines is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%